(untitled) (Ágora de Heterodoxias, 2026)
The evolution of public deliberation spaces can be understood through an analogy that connects three historical and conceptual scenarios: the Greek agora, postmodern democracy, and the academic realm of a peer-reviewed journal. Although different in form and context, these spaces share the same structural function, which is to serve as devices for the production, confrontation, and validation of ideas within a community. The agora, in classical Greece, was the core of political and social life. There, citizens exercised their right to speak in an environment of direct interaction, where persuasion, debate, and rhetoric were fundamental tools for the construction of the public sphere. This space embodied an original notion of freedom linked to active participation, though limited by the exclusions of its time.